2016
DOI: 10.1039/c6ra21462b
|View full text |Cite
|
Sign up to set email alerts
|

Composition profiles, monthly changes and health risk of PCDD/F in fly ash discharged from a municipal solid waste incinerator (MSWI) in Northeast China

Abstract: Monthly changes and health risk of PCDD/Fs in fly ash which was one of hazardous wastes from municipal solid waste incinerator (MSWI) were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…As one group of POPs, polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) were widespread in environment (Barghi et al, 2016;Fernandez-Gonzalez et al, 2015;Li et al, 2016a;2016b;Schuhmacher et al, 2013Schuhmacher et al, , 2014Squadrone et al, 2016). Stockholm Convention indicated that medical waste incinerator (MWI) was a key source of PCDD/Fs emission.…”
Section: Introductionmentioning
confidence: 99%
“…As one group of POPs, polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) were widespread in environment (Barghi et al, 2016;Fernandez-Gonzalez et al, 2015;Li et al, 2016a;2016b;Schuhmacher et al, 2013Schuhmacher et al, , 2014Squadrone et al, 2016). Stockholm Convention indicated that medical waste incinerator (MWI) was a key source of PCDD/Fs emission.…”
Section: Introductionmentioning
confidence: 99%